Beyond auditory sensitivity: cognitive and linguistic influences on clinical performance in post-lingual adult cochlear implant users - Nadine Buczak; Nadine Buczak; Eugen Kludt; Eugen Kludt; Thomas Lenarz; Thomas Lenarz; Andreas Büchner; Andreas Büchner (Frontiers in Audiology and Otology)
IntroductionSpeech understanding in cochlear implant (CI) users is influenced by various factors, particularly cognitive and linguistic abilities. While previous studies have explored both bottom-up and top-down processes in speech comprehension, this study focuses specifically on the role of cognitive and linguistic factors in shaping speech recognition outcomes in post-lingually deafened adults.MethodsFifty-eight post-lingually deafened adults, with at least 12 months of CI experience, participated in this study using a previously established dataset. Participants were categorized into Poor Performers (n = 25; ≤ 35% word recognition at 65 dB SPL) and Good Performers (n = 33; ≥65% word recognition at 65 dB SPL). Participants with single-sided deafness were excluded to avoid confounding effects. Cognitive and linguistic variables, including vocabulary size (Wortschatztest, WST), processing speed (Symbol Digit Modality Test, SDMT), and executive control (Stroop Test), were assessed. Descriptive statistics were calculated to explore group differences, and Cohen's d was used to assess effect sizes. Statistical tests included univariate linear regression for individual predictors and multiple linear regression for the overall model.ResultsThe results indicated that larger vocabulary size, faster processing speed, and higher educational level were significantly associated with better speech performance. Additionally, younger age at testing correlated with improved outcomes, while early onset hearing loss (before age 7) was linked to poorer performance.DiscussionThese findings emphasize the critical influence of cognitive and linguistic abilities, early auditory experiences, and educational background on CI outcomes. Together, these factors significantly predict speech understanding, highlighting the need to consider them in rehabilitation planning and comprehensive assessments to guide targeted interventions.